Computerized Dynamic Posturography: Comparison of Results Obtained from Individuals with Symptomatic Osteoarthritis of the Knee and Controls - Hyoungjin Park (Asociación Española de Ciencias del Deporte, 2018)
Introduction: The purpose of this study was to compare the balance of individuals with knee OA and healthy peers and to determine the effect of knee OA on balance by matching gender, age, mass, height, and BMI. Material and Methods: Thirty-two individuals, sixteen with knee osteoarthritis and sixteen healthy, were evaluated on balance as measured by a NeuroCom EquiTest Sensory Organization Test and Motor Control test protocol. Outcomes included an equilibrium composite score, equilibrium scores on six sensory conditions, and sensory ratios for visual, somatosensory, vestibular systems as well as ability to manage altered proprioceptive inputs. Results: The healthy knee group showed that significantly higher equilibrium scores, higher strategy scores, higher sensory analysis ratios, and faster latency in the analysis of sensory organization test and motor control test. Conclusion: The existence of knee OA affected the effectiveness of the sensory system and the use of this signal in maintaining body balance.